All in the mix race, class and school choice - Byrne, Bridget; De Tona, Carla (Manchester University Press, 2019)
All in the mix: class, race and school choice considers how parents choose secondary schools for their children and makes an important intervention into debates on school choice and education. The book examines how parents talk about race, religion and class - in the process of choosing. It also explores how parents' own racialised and classed positions, as well as their experience of education, can shape the way they approach choosing schools. Based on in-depth interviews with parents from different classed and racialised backgrounds in three areas in and around Manchester, the book shows how discussions about school choice are shaped by the places in which the choices are made. It argues that careful consideration of choosing schools opens up a moment to explore the ways in which people imagine themselves, their children and others in social, relational space